2022
DOI: 10.1186/s12891-022-05039-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the relapse in Ponseti treated congenital clubfoot

Abstract: Objectives We retrospectively investigated the clinical materials to seek the factors that lead to relapse after using the Ponseti method. Methods We retrospectively reviewed all children with congenital clubfoot treated with the Ponseti method in our hospital from June 2008 to June 2013. The data included the following factors: age, gender, initial Pinari score, number of casts, number of feet (unilateral or bilateral), age at the first casting, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…However, a common question that is usually raised is, "What factors are associated with relapse?" [34]. In our study we found a relapse rate of 9.1%.…”
Section: Discussionsupporting
confidence: 54%
“…However, a common question that is usually raised is, "What factors are associated with relapse?" [34]. In our study we found a relapse rate of 9.1%.…”
Section: Discussionsupporting
confidence: 54%
“…Non-compliance with post tenotomy bracing, educational level (less than high school) of parents, inaccess of the parents to the internet were some of the factors that affect outcome after the use of the Ponseti method for the management of idiopathic clubfoot while age and sex of the patients was not found to have a significant effect on the recurrence of the deformity [ 10 ]. The initial Pirani score, compliance with the foot abduction brace and the age at the first casting are three independent factors for relapse in clubfoot [ 11 ]. Non-compliance and the educational level of the parents (high-school education or less) are significant risk factors for the recurrence of clubfoot deformity after correction with the Ponseti method [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies focus on relapse before age 4 3,8,11–13. Fewer have reported on relapse in later childhood 4,7,14,15. In addition, little research has focused on late relapse, comparing those treated with the Ponseti method with those treated with joint sparing and joint invasive surgeries after initial casting treatment.…”
mentioning
confidence: 99%
“…3,8,[11][12][13] Fewer have reported on relapse in later childhood. 4,7,14,15 In addition, little research has focused on late relapse, comparing those treated with the Ponseti method with those treated with joint sparing and joint invasive surgeries after initial casting treatment. The purpose of this study was to compare gait characteristics of children with late clubfoot relapse (defined as ≥ 5 y of age) following treatment with the Ponseti method compared with intra-articular (posteromedial release) and extra-articular (joint sparing) surgery.…”
mentioning
confidence: 99%
See 1 more Smart Citation